DEVELOPMENT OF A CONCEPTUAL FRAMEWORK FOR TEACHER DEVELOPMENT BASED ON THE CONCEPT OF LEARNING FACILITATOR - Rungsiriwat, Waree; Usaho, Chayapim; ๋Jariyarangsiroge, Apiradee (Journal of Educational Review Faculty of Education in MCU, 2023)
This research article is documentary research with the objective to develop 2 conceptual frameworks which are 1) Learning facilitator and 2) Teacher development. The documentary synthesis method was used in this study. The research instrument included content analysis, frequency analysis from 11 documents. The research findings are divided into 2 conceptual frameworks: 1) The skills of learning facilitator, which consists of safe learning environment creation skill and lifelong learning promotion skill; 2) Teacher development consists of 2 main types which are on-the-job development and off-the-job development.